2022
DOI: 10.3389/fonc.2022.1014888
|View full text |Cite
|
Sign up to set email alerts
|

FCGR3A: A new biomarker with potential prognostic value for prostate cancer

Abstract: To screen target gene cluster by bioinformatics analysis and verify them by in vitro experiment and clinicopathological correlation analysis. We try to find a new biomarker with prognostic value for prostate cancer (PCa). 42 candidate marker genes were constructed by protein protein interaction (PPI) network and enriched by KEGG pathway to find out the gene cluster we are interested in. Prognostic model was established to preliminarily analyze the prognostic value of this gene cluster in PCa, and Cox risk regr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 43 publications
0
0
0
Order By: Relevance
“…It encodes a transmembrane receptor that allows the immune cells to recognize and kill targeted cells [47]. Recently, researchers have found that FCGR3A is highly expressed in pan-cancer, including PCa, and it could be an independent biomarker for PCa patients [39,48]. In this study, FCGR3A was identified as a hub gene and prognosis-related gene via PPI and Cox regression analyses.…”
Section: Discussionmentioning
confidence: 84%
“…It encodes a transmembrane receptor that allows the immune cells to recognize and kill targeted cells [47]. Recently, researchers have found that FCGR3A is highly expressed in pan-cancer, including PCa, and it could be an independent biomarker for PCa patients [39,48]. In this study, FCGR3A was identified as a hub gene and prognosis-related gene via PPI and Cox regression analyses.…”
Section: Discussionmentioning
confidence: 84%